Penerapan Model PBL Berbantuan Media Pembelajaran Interaktif untuk Meningkatkan Kemampuan Berpikir Kritis Siswa - Noviyanti, Baiq Elisa; Baidowi; Salsabila, Nilza Humaira; Turmuzi, Muhammad (FKIP Universitas Mataram, 2024)
This study aims to determain to increase the student’s ability to think more critize in number pattern material matery class VIII MTsN 1 Lombok Barat 2023/2024 with PBL model with interactive lesson media. The methode that used in this research is experimental methode. This research have been taken in two classes, the first one is experimental class and the other one is control class. The experiment class is used PBL model with interactive lesson media. Meanwhile, the control class is used PBL model. The instrument that used in this research is interactive PPT and the instrument that used in collecting data is the ability test of critical thinking. The average score of theexperimental class was 72.03 and the average score of the controlclass was 59.72. This means that learning using the PBL model assisted by interactive learning media is more effective than learning using the PBL model. The initial average score ofexperimental class students was 67.55 after applying the PBLmodel assisted by interactive learning media obtained an averagescore of 72.03. This shows that there is an increase of thestudent’s in critical thinking skills of number pattern material ofgrade VIII MTsN 1 Lombok Barat 2023/2024 after applying thePBL model assisted by interactive learning media.